Carter's®, Inc. and Organic Cotton - Burns,Leslie D; Mullet,Kathy (2018)
The business problem of adding a line of organic cotton products is speculative only and not based on publicly available and/or documented information from Carter’s, Inc.
Keywords: Design Program